2017
DOI: 10.1186/s13068-017-0795-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of RAV1-engineering on poplar biomass production: a short-rotation coppice field trial

Abstract: BackgroundEarly branching or syllepsis has been positively correlated with high biomass yields in short-rotation coppice (SRC) poplar plantations, which could represent an important lignocellulosic feedstock for the production of second-generation bioenergy. In prior work, we generated hybrid poplars overexpressing the chestnut gene RELATED TO ABI3/VP1 1 (CsRAV1), which featured c. 80% more sylleptic branches than non-modified trees in growth chambers. Given the high plasticity of syllepsis, we established a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…Previous results of our laboratory reported that overexpression of CsRAV1 in poplar increased axillary bud outgrowth under LDs (Moreno-Cortés et al, 2012;Moreno-Cortés et al, 2017). Similarly, we found that poplar RAV1oe increased axillary bud outgrowth under LD conditions (Fig.…”
Section: Poplar Orthologs Of Constans and Tempranillo Show Diverged Features In The Regulation Of Ft Between Poplar And Arabidopsissupporting
confidence: 85%
See 1 more Smart Citation
“…Previous results of our laboratory reported that overexpression of CsRAV1 in poplar increased axillary bud outgrowth under LDs (Moreno-Cortés et al, 2012;Moreno-Cortés et al, 2017). Similarly, we found that poplar RAV1oe increased axillary bud outgrowth under LD conditions (Fig.…”
Section: Poplar Orthologs Of Constans and Tempranillo Show Diverged Features In The Regulation Of Ft Between Poplar And Arabidopsissupporting
confidence: 85%
“…Functional studies performed in our laboratory indicated that the overexpression of chestnut RAV1 increased axillary branching under LDs, however the molecular mechanism involved has yet to be determined (Moreno-Cortés et al, 2012;Moreno-Cortés et al, 2017). Similarly, in this thesis, it is shown that overexpression of the poplar RAV1 promoted both higher levels of FT2 gene expression and axillary bud outgrowth under LDs.…”
Section: Ft2 Could Promote Poplar Axillary Bud Outgrowthmentioning
confidence: 53%
“…Overexpression of CsRAV1, a chestnut ortholog of TEMPRANILLO , a regulator of FT ( Castillejo and Pelaz, 2008 ), led to upregulation of a poplar ortholog of FT ( PttFT2 ) expression ( Triozzi et al, 2018 ) and consequently to increased branching both under greenhouse and field conditions ( Moreno-Cortes et al, 2012 , 2017 ). Under field conditions, increased branching led to increased biomass ( Moreno-Cortes et al, 2017 ). Similarly, overexpression of a poplar ortholog of GIGANTEA, a positive regulator of FT , upregulated PttFT2 and increased sylleptic branching in poplar ( Ding et al, 2018 ).…”
Section: Manipulation Of Crown Architecturementioning
confidence: 99%
“…Light conditions are of great importance to them in the process of photosynthesis, and, more precisely, its intensity which increases in direct proportion to the intensity of light (Dickmann et al, 2001). In current studies of trees of the genus Populus, researchers mostly focus on using them as biomass, which is a source of renewable energy (Moreno-Cortés et al, 2017;Aylott et al, 2008), on using their wood for construction and industry purposes (Kretschmann et al, 1999), and on pulp for the pulp and paper industry (Przybysz and Przybysz, 2013), as well as its application in the pharmaceutical industry (Belkhodja et al, 2016). Many studies focus on the efficiency of poplar cultivation as related to different lengths of production cycles (Pereira et al, 2016;Lamerre et al, 2015;Moreno-Cortés et al, 2017).…”
Section: Introductionmentioning
confidence: 99%